Concept and essence of heuristic teaching (Pedagogy of Higher and Secondary Education, 2007)
The concept of heuristic, heuristic teaching in philosophical, psychological and pedagogical aspects is examined in this article.
Keywords: heuristic; heuristic teaching; creative development and self-development